Measuring the Burden: The Effect of Travel Distance on Abortions and Births - Caitlin Knowles Myers (Institute of Labor Economics (IZA), 2021)
I compile and disseminate novel panel data sets measuring county-level travel distances to abortion facilities and resident abortion rates. Using these data and exploiting temporal and spatial variation in distances, I implement difference-in-difference research designs measuring the causal effects of distance to the nearest abortion facility. The results indicate large and non-linear effect: An increase in travel distance from 0 to 100 miles—a level that courts have generally treated as not unduly burdensome for women seeking abortions—is estimated to prevent 20.5% of women seeking an abortion from reaching a provider, and in turn to increase births by 2.4%.
Keywords: I11; I12; J13; 330; travel distance; abortions; births